2020
DOI: 10.1016/j.pedneo.2020.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variation status and enzyme activity for UDP-glucuronosyltransferase 1A1 gene on neonatal hyperbilirubinemia

Abstract: Pediatrics and Neonatology (2020) 61, 506e512 reconfirm that the À53 A(TA) 7 TAA/A(TA) 7 TAA is not, while the 211AA is a risk factor for the development of neonatal hyperbilirubinemia in Taiwanese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…6 Huang et al have verified this correlation in partially and exclusively breastfed neonates, and they concluded that the homozygous variation 211AA was a risk factor for the development of NH in the Taiwanese. 7 These results indicated that UGT1A1 gene variants, especially at nucleotide 211 (G > A), play a major role in the development of serious NH.…”
Section: Investigating Whether Screening or Testing For The Variationmentioning
confidence: 87%
See 1 more Smart Citation
“…6 Huang et al have verified this correlation in partially and exclusively breastfed neonates, and they concluded that the homozygous variation 211AA was a risk factor for the development of NH in the Taiwanese. 7 These results indicated that UGT1A1 gene variants, especially at nucleotide 211 (G > A), play a major role in the development of serious NH.…”
Section: Investigating Whether Screening or Testing For The Variationmentioning
confidence: 87%
“…Because it is difficult to measure the accurate UGT 1A1 enzyme activity in each neonate with NH, Huang et al used an estimated enzyme activity model depending on a combination of SNPs to predict the correlation between UGT1A1 gene polymorphism and NH. 7 They concluded that the estimated enzyme activity in the UGT1A1 gene could not be used to explain the development of NH. This result means that there are factors other than UGT1A1 gene polymorphism that may contribute to the development of NH.…”
Section: Investigating Whether Screening or Testing For The Variationmentioning
confidence: 99%
“…(TA) 7 TAA/A(TA) 7 TAA SNV, 1,56,58 and À53A(TA) 7 TAA/A(TA) 7 TAA was associated with À3279GG. 1,3,66,68 However, À53A(TA) 6 TAA>A (TA) 7 TAA was not associated with 686C>A, 1,10,30,[54][55][56]58,59,66,67 and À3279T>G was not associated with À53A(TA) 6 TAA>A (TA) 7 TAA. 1,3,34,66,69 In these relationships, the degree of linkage disequilibrium (D 0 ) was high, whereas r 2 was low for the association between À3279G and À53A(TA) 7 TAA (D 0 = 0.95, r 2 = 0.26) and between À53A(TA) 7 TAA and 686A (D 0 = 0.95, r 2 = 0.13).…”
Section: Linkage Disequilibriummentioning
confidence: 89%
“…68 In this review, we observed that the 686 CA genotype was associated with the À53A(TA) 6 TAA/A(TA) 7 TAA or À53A(TA) 7 TAA/A(TA) 7 TAA SNV. 1,10,30,[54][55][56]58,59,66,67 When À3279T>G was considered, 686CA was observed to be closely associated with not only À53A(TA) 6 TAA/ A(TA) 7 TAA or À53A(TA) 7 TAA/A(TA) 7 TAA but also À3279TG or À3279GG. 1,66 The 686AA genotype was associated with the À53A…”
Section: Linkage Disequilibriummentioning
confidence: 99%
“…The variation in A(TA) 6 TAA>A(TA) 7 TAA at nucleotide -53 in the UGT1A1 gene plays a significant role in the development of neonatal hyperbilirubinemia in Caucasians and some Asian populations, such as Indians [19] and Malaysians [20]. However, in East-Asian populations, such as Chinese, Japanese and Taiwanese, 211 AA genotype is the main cause of neonatal hyperbilirubinemia, whereas -53 A(TA) 7 TAA/A(TA) 7 T AA seems to have a protective effect against hyperbilirubinemia development in neonates fed with breast milk [21]. Breast milk jaundice can be differentiated from breast feeding jaundice that is characterized by decreased fluid intake and increased entero-hepatic recirculation of unconjugated and deconjugated bilirubin in breast-fed babies during the early days of life [22].…”
Section: Neonatal Hyperbilirubinemiamentioning
confidence: 99%